Special edition using Microsoft Office Word 2007 - Wempen, Faithe (Special edition., 2006)
A resource for experienced users showcases the new features of the latest edition of the word processing software, explaining how to use the user interface, the various tools and techniques that can be used to complete complex projects, and how to createdetailed and visually appealing documents.